Kebijakan Keuangan Inklusif Dalam Perspektif Ekonomi Syariah - Efrita Norman (LPPM Institut Nasional Laa Roiba Bogor, 2020)
This study aims to explore inclusive financial policies in the perspective of Islamic economics. The method used is a qualitative method with a literacy study and mass media analysis approach. Hasilnuya, Indonesia (BI) as the monetary authority believes the NSFI program as the main way to improve financial literacy in order to increase the ability of individuals to manage their finances. The banking sector as the majority of financial services activities in Indonesia is a front liner for the program. The strategies used in achieving financial inclusion goals include five pillars, namely financial education, increasing financial eligibility, supporting regulations, increasing intermediation facilitation, and policy reforms covering customer protection, banking agents, and phone banking. Going forward, the financial industry needs to map the potential of the community and business sector as targets of the financial inclusion program. For this reason, a comprehensive partisanship and strategy from the financial industry is needed to expand access to services for the community, especially in preparing products that can meet the savings and investment needs of the community. Keywords: Bank Indonesia, Islamic economics, financial inclusion, monetary authority.